2022
DOI: 10.3390/healthcare10020379
|View full text |Cite
|
Sign up to set email alerts
|

“Wire Syndrome” Following Bonded Orthodontic Retainers: A Systematic Review of the Literature

Abstract: (1) Background and objective: Tooth movements described as unexplained, aberrant, unexpected, unwanted, or undesirable can occur in the presence of an intact orthodontic retention wire, without detachment or fracture. This iatrogenic phenomenon, known little or not by many practitioners, responsible for significant dental and periodontal complications, both functional and aesthetic, is called “Wire Syndrome” (WS). It is therefore considered an undesirable event of bonded orthodontic retainers, which must be di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The movements caused by WS do not correspond to a relapse or a physiological process [21]; the effects of WS on teeth are not correlated with the position of teeth before orthodontic treatment nor with their position at the time of the debonding of an orthodontic appliance. WS can therefore be considered as a new malocclusion observed after the placement of a fixed, bonded, post-orthodontic retainer [21]. The aim of this article was to show, via three clinical cases representing three main situations of WS of increasing complexity, the relevance of the early diagnosis of this syndrome.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The movements caused by WS do not correspond to a relapse or a physiological process [21]; the effects of WS on teeth are not correlated with the position of teeth before orthodontic treatment nor with their position at the time of the debonding of an orthodontic appliance. WS can therefore be considered as a new malocclusion observed after the placement of a fixed, bonded, post-orthodontic retainer [21]. The aim of this article was to show, via three clinical cases representing three main situations of WS of increasing complexity, the relevance of the early diagnosis of this syndrome.…”
Section: Discussionmentioning
confidence: 93%
“…The first systematic review on wire syndrome (WS) was published by Charavet et al [21] in 2022, defining its prevalence and associated characteristics. This review involved an electronic search strategy on four databases supplemented by a manual search.…”
Section: Authors Date Namementioning
confidence: 99%
“…116 This "wire syndrome" may present in different degrees of severity and depends on the amount of incisor inclination and torque differences. 117 Reported prevalence rates are up to 30%. 118 These unwanted adverse effects of OT in the retention phase should be viewed at least as complications and if left unnoticed and/ or unaddressed in their early stages should be considered as treatment errors.…”
Section: Bony Envelopementioning
confidence: 99%
“…Accordingly, gingival recession with root exposure might occur as a consequence of a root position outside the bony envelope 116 . This “wire syndrome” may present in different degrees of severity and depends on the amount of incisor inclination and torque differences 117 . Reported prevalence rates are up to 30% 118 …”
Section: Ot In Relation To Mucogingival Conditionmentioning
confidence: 99%
“…The increasing demand for orthodontic therapies that lead to buccal displacement of the mandibular incisor roots, associated with the thin buccal cortical bone, facilitates the appearance of gingival recessions [ 4 ]. Additionally, a recent systematic review reported unexpected dental movements after orthodontic treatment has finished—caused by the wire retainers and resulting in dental and periodontal complications—termed “wire syndrome” [ 5 ]. Clinicians may also encounter aberrant frenula with a very coronal attachment, high muscle attachments, a larger avascular surface area, tooth malposition, shallow vestibules and/or thin gingival phenotype [ 1 , 2 , 6 ].…”
Section: Introductionmentioning
confidence: 99%